PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA,DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SALTTEK DUMPANG JAYA - Azmi, Muhammad Alfi; Yuriadi (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine the effect of Work Motivation, Work Environment, and Work Discipline on Employee Performance. This study uses a quantitative method with questionnaire and interview data collection techniques. The number of samples was drawn using the total sampling technique. Data management uses SPSS Version 25 software. Based on the study, it shows that Work Motivation on Employee Performance is obtained from the t-value -2.668 < t-table 1.684. So Work Motivation partially shows that it does not have a positive and significant effect on Employee Performance. In the Work Environment, the t-value is 5.952> t-table 1.684. So the Work Environment partially has a positive and significant effect on Employee Performance. In Work Discipline, the t-value is 3.688> t-table 1.684. So the basis of the partial test provisions is that Work Discipline has a positive and significant effect on Employee Performance. Based on the F-value = 36.227 while the F-value = at a = 0.05 with n = 43, the F-value is obtained. The results show that F count > F table, i.e., 36,227 > 2.85. Therefore, it can be concluded that work motivation, work environment, and work discipline collectively influence employee performance at PT. Salttek Dumpang Jaya.